PROGRAM JUMANTIK CILIK TANGGAP BOCAH DALAM PEMBERANTASAN SARANG NYAMUK DI PUSKESMAS SLEMAN, KABUPATEN SLEMAN - Rusita Nurwidi Astuti; Hari Kusnanto; Retna Siwi Padmawati (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Dengue fever (DHF) is an endemic disease in Sleman District. Number of dengue cases up to December 2014 recorded 538 cases (IR 50,6/100,000 population) with the death of 4 people (CFR 0,7%). One village in the region of Sleman Primary Health Care (PHC) always have dengue cases annually are Caturharjo village. On that basis Sleman PHC forming and pioneering activities childrens larva observer named Tanggap Bocah (TABO) consisting of primary school and secondary school children with built hamlets first is Ganjuran Hamlet, Village Caturharjo and became active in 2012. TABO itself is expected to encourage community participation in dengue mosquito nest eradication, reduce DHF morbidity and improve ABJ in Village Caturharjo. Objective: The objective of this research is to get an overview of monitoring the implementation of the TABO in Sleman PHC. Methods: This study is a qualitative research with case study design. Results: Implementation of PJB by Jumantik TABO on PSN DBD as a form of community participation among children in the prevention of dengue disease with the primary goal of planting clean and healthy behavior (PHBS) early. Although no special training is given in addition to coaching and monitoring, Jumantik TABO willing and able as extension for friends, families and society as individuals. The increase in dengue cases and decrease in ABJ indicate a change in behavior and community participation in PSN as a result of activities Jumantik TABO. Conclusions: Implementation TABO in the prevention of dengue fever in the village Caturharjo running effectively and according to expectations with the declining number of DHF cases and increasing ABJ and behavioral changes in the community in PSN DBD and PHBS.